Performance study of single phase reclosing using simplified arc model on the Thailand 500 kV system - K. Ngamsanroaj (2018)
THE interaction between a fault arc and the power system has a big influence on evaluation of sucessful reclosing of a faulted system. In this paper, the single phase reclosing performance of the system is considered using Thailand 500 kV transmission system between Mae Moh and Tha Ta Ko substations as examples. The work has been investigated using simplified arc model. The study has used EMTP simulation to analyse the behavior of the system response to switching operation. The illustrative cases are also presented in order to determine approximately the maximum arc duration that may be expected.